Analysis of The Effect of Price Perception, Promotion Media, And Ease of Processing on customer decisions in utilizing PLN’s Power-Up Promo Program at PT PLN (Persero) UP3 Pasuruan - Fauzi, Mochamad Rizal; Suryaputra, Ronald (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines the influence of price perception, promotional media, and ease of process on customer decisions to use the power-added promotional program at PT PLN (Persero) UP3 Pasuruan. Amid increasing electricity demand driven by technological advancement and economic growth, effective promotional strategies are required to improve service quality and electricity sales. Background Problems: Although the power-added promotional program has been implemented as a strategic initiative, customer participation at PLN UP3 Pasuruan remains suboptimal. This condition is associated with differences in customer price perceptions, limited utilization of promotional media, and perceived complexity in the service process, which may hinder customer decision-making. Research Methods: This study employs a quantitative approach using a survey method. Data were collected through structured questionnaires distributed to 260 respondents. The data were analyzed using multiple linear regression with SPSS version 26 to examine the partial and simultaneous effects of the independent variables on customer decisions. Findings/Results: The results indicate that price perception, promotional media, and ease of process each have a positive and significant effect on customer decisions, both partially and simultaneously. Conclusion: The study concludes that transparent pricing information, effective use of diverse promotional media, and simplified service processes are crucial in enhancing customer decisions and participation in power-added promotional programs.